Red slip pottery from Laodicea/Phrygia - Duman, Bahadir (Rei Cretariae Romanae Fautorum Acta, 2015)
Laodicea is located on the western tip of the Phrygia region, 6 km northwest of the Denizli Province and sits on a relatively high platform amidst a topographically rugged terrain. The archaeological excavations at the site that started in 2003 have unearthed structures in approximately a 4 square kilometer area and include the Columned Main Street (Syria Boulevard), Nymphaeum A (Fountain of Septimius Severus), Temple A (Sebasteion), Central Bath, Western Theatre, Eastern Byzantine Gate, Northern and Eastern Towers of the Eastern Byzantine Gate, South Roman Villa, Northern Workshop, Stadium Street, Nymphaeum B, Latrina, Asopos Hill, Northern Theatre the Stadium and necropoli scattered throughout the city. Whether in context or by landfill, examples of Eastern Sigillata and Late Roman Red Slip Ware found inside the stratigraphic layers of the before mentioned structures during the excavations, provide valuable insight for the utilization stages of structures found at Laodicea. Pottery like Eastern Sigillata A, Eastern Sigillata B, Eastern Sigillata C, Cypriot Sigillata, Sagalassos Red Slip Ware and African Sigillata, which are commonly found in many ancient cities excavated around Anatolia, are also found in excavations at Laodicea. Examples from the mentioned pottery groups make up a portion of imported material used in Laodicea.